The Effect of Commitment and Work Ability on Employee Performance at Shopeexpress Helvetia - Sulianingsih, Ladiva Eka; Wahyuni, Neni Sri; Bakhtiar, Bakhtiar; Sonata, Ilham (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2025)
This study aims to determine the effect of Commitment and Work Ability on Employee Performance in the Office. The population and sample of this study were all 60 employees. The sampling technique used the Slovin Formula. Data collection techniques used were questionnaires, literature studies and documentation studies. The results of this study Commitment has a positive and significant effect on Employee Performance at Shopeexpress Helvetia, Work Ability has a positive and significant effect on Employee Performance at Shopeexpress Helvetia, Commitment and Work Ability have a positive and significant effect on Employee Performance at Shopeexpress Helvetia.